Characteristics of Yalimo Papua Kinang Jingkion powder as filler in HRS-WC mixture - Bahtiar Bahtiar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Kinang Jingkion is the name of an area in Yalimo Regency, Papua, that has unique material deposits with specifications that make it suitable for use as aggregate in pavements, including as filler in powder form. The high cost of construction in the Yalimo region and generally in the Papua Mountains is due to logistics, where materials such as cement and asphalt are mobilized by airplane. With the alternative use of local filler material, it will eliminate the long and expensive mobilization. This study aims to analyze the characteristics of Yalimo Papua kinang jingkion powder and determine whether it can be used as a filler material in HRS-WC mixtures. The method was carried out by Marshall testing to obtain stability and adhesion values. The test method was carried out in accordance with General Specifications Revision 2 of 2018, the Directorate General of Highways, and Indonesian National Standards (SNI) for each test, including asphalt, coarse and fine aggregates, and Kinang Jingkion material. The optimal asphalt content (OAC) obtained from Kinang Jingkion filler is 6.85%. Based on the results of the research and discussion that have been described, it is concluded that the results of the Marshall characteristics test for Kinang Jingkion Filler at 6.85% asphalt content show a stability value of 1194.40 Kg, MQ 460.2 Kg/mm, VIM 2.68%, and VFB 80.16.